Sustainability Analysis of Coffee Farming Business Based On Economic, Social, And Technological Dimensions - Baharuddin; Fitriyah , Andi Tenri; Sheyoputri , Aylee Christine Alamsyah; Suhartati; Ahmad, Ahfandi (Universitas Muhammadiyah Yogyakarta, 2025)
The study aims to assess the sustainability of coffee farming businesses in Sarang-Sarang Village, Sa'dan District, North Toraja, and South. 48 individuals were selected as the samples through simple random sampling, representing 10% of the population. Using a descriptive quantitative approach, the study measured the economic, social, and technological dimensions of coffee farming business sustainability. Data was collected through a 4-point Likert scale with the following categories: 4) Good, 3) Fair, 2) Poor, and 1) Very Poor. The applied data analysis involves scoring. The measured dimensions encompass economic, social, and technological dimensions. The findings suggested that the social dimension of coffee farming business sustainability in Sarang-Sarang Village, Sa'dan District, North Toraja, can be generally categorized as good. Most coffee farmers in Sarang-Sarang Village owned land areas of approximately 3-5 hectares, accounting for 77.27% of the total area. A smaller proportion of farmers (22.73%) owned land areas of 6–8 hectares. The revenue generated by the coffee farming business in the village ranged from Rp2, 000,000 to Rp4, 000,000 on average.